Postural evaluation of patients with temporomandibular disorders under use of occlusal splints - Strini, Paulinne Junqueira Silva Andresen (2009)
OBJECTIVES: Alterations in the temporomandibular complex can reflect in adaptations of the individual's entire muscular system, intervening with the head position and scapular waist, developing postural alterations and modifying all corporal biomechanics. The aim of this study was to evaluate the head position (HP) and head postural alterations before and after installation of occlusal splints. MATERIAL AND METHODS: Twenty patients with temporomandibular disorders (TMD) underwent clinical and postural examination, before the installation of an occlusal splint, and after 1 week and 1 month of use. RESULTS: There were statistically differences for HP, between the initial values and after 1 week of use of the occlusal device (p= 0.048) and also between 1 week and 1 month of evaluation (p= 0.001). Decrease of the painful symptomatology and maintenance of the rectification were also observed. CONCLUSIONS: The individual's postural position can suffer biomechanical alterations due to stomatognathic alterations, causing clinically visible changes in dysfunctional individuals and affecting the performance of the involved structures.